AML-derived exosomes promote induction of myeloid-derived suppressor cells in an mTOR-signaling-dependent fashion - Jitschin, R.; Tohumeken, Sehmus; Saul, D.; Bruns, Heiko; Braun, Martina; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

CD33/CD3-bispecific T-cell engaging (BiTE®) antibody construct targets monocytic AML myeloid-derived suppressor cells - Jitschin, Regina; Saul, Domenica; Braun, Martina; Tohumeken, Sehmus; Kischel, Roman; Lutteropp, Michael; Dos Santos, Cedric; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (Journal for ImmunoTherapy of Cancer, 2018)
Acute myeloid leukemia (AML) is the most common acute leukemia amongst adults with a 5-year overall survival lower than 30%. Emerging evidence suggest that immune alterations favor leukemogenesis and/or AML relapse thereby negatively impacting disease outcome. Over the last years myeloid derived suppressor cells (MDSCs) have been gaining momentum in the field of cancer research. MDSCs are a heterogeneous cell population morphologically resembling either monocytes or granulocytes and sharing some key features including myeloid origin, aberrant (immature) phenotype, and immunosuppressive activity. Increasing evidence suggests that accumulating MDSCs are involved in hampering anti-tumor immune responses and immune-based therapies. Here, we demonstrate increased frequencies of CD14+ monocytic MDSCs in newly diagnosed AML that co-express CD33 but lack HLA-DR (HLA-DRlo). AML-blasts induce HLA-DRlo cells from healthy donor-derived monocytes in vitro that suppress T-cells and express indoleamine-2,3-dioxygenase (IDO). We investigated whether a CD33/CD3-bispecific BiTE® antibody construct (AMG 330) with pre-clinical activity against AML-blasts by redirection of T-cells can eradicate CD33+ MDSCs. In fact, T-cells eliminate IDO+CD33+ MDSCs in the presence of AMG 330. Depletion of total CD14+ cells (including MDSCs) in peripheral blood mononuclear cells from AML patients did not enhance AMG 330-triggered T-cell activation and expansion, but boosted AML-blast lysis. This finding was corroborated in experiments showing that adding MDSCs into co-cultures of T- and AML-cells reduced AML-blast killing, while IDO inhibition promotes AMG 330-mediated clearance of AML-blasts. Taken together, our results suggest that AMG 330 may achieve anti-leukemic efficacy not only through T-cell-mediated cytotoxicity against AML-blasts but also against CD33+ MDSCs, suggesting that it is worth exploring the predictive role of MDSCs for responsiveness towards an AMG 330-based therapy.
EVALuna2:35089

CLL-cells induce IDOhi CD14+HLA-DRlo myeloid-derived suppressor cells that inhibit T-cell responses and promote TRegs - Jitschin, Regina; Braun, Martina; Büttner, Maike; Dettmer-Wilde, Katja; Bricks, Juliane; Berger, Jana; Eckart, Michael J.; Krause, Stefan; Oefner, Peter J.; Le Blanc, Katarina; Mackensen, Andreas; Mougiakakos, Dimitrios (Blood, 2014)
Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous population that shares certain characteristics including an aberrant myeloid phenotype and the ability to suppress T cells. MDSCs have been predominantly studied in malignant diseases and findings suggest involvement in tumor-associated immune suppression. Chronic lymphocytic leukemia (CLL) is the leukemia with the highest incidence among adults. Immune defects occur already at early disease stages and impact the clinical course. We assessed presence, frequency, association to other immune parameters, and functional properties of circulating CD14(+) cells lacking HLA-DR expression (HLA-DR(lo)) in patients with untreated CLL. These monocytic cells represent one of the best-defined human MDSC subsets. Frequency of CD14(+)HLA-DR(lo) cells was significantly increased in CLL patients. Furthermore, MDSCs suppressed in vitro T-cell activation and induced suppressive regulatory T cells (TRegs). The MDSC-mediated modulation of T cells could be attributed to their increased indoleamine 2,3-dioxygenase (IDO) activity. CLL cells induced IDO(hi) MDSCs from healthy donor monocytes suggesting bidirectional crosstalk between CLL-cells, MDSCs, and TRegs. Overall, we identified a MDSC population that expands in CLL. The exact mechanisms responsible for such accumulation remain to be elucidated and it will be of interest to test whether antagonizing suppressive functions of CLL MDSCs could represent a mean for enhancing immune responses.
EVALuna2:25463

Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25

Stromal cell-mediated glycolytic switch in CLL cells involves Notch-c-Myc signaling - Jitschin, Regina; Braun, Martina; Qorraj, Mirjeta; Saul, Domenica; Le Blanc, Katarina; Zenz, Thorsten; Mougiakakos, Dimitrios (Blood, 2015)
It is well established that the stromal niche exerts a protective effect on chronic lymphocytic leukemia (CLL) cells, thereby also affecting their drug sensitivity. One hallmark of malignant cells is metabolic reprogramming, which is mostly represented by a glycolytic shift known as the Warburg effect. Because treatment resistance can be linked to metabolic alterations, we investigated whether bone marrow stromal cells impact the bioenergetics of primary CLL cells. In fact, stromal contact led to an increase of aerobic glycolysis and the cells' overall glycolytic capacity accompanied by an increased glucose uptake, expression of glucose transporter, and glycolytic enzymes. Activation of Notch signaling and of its direct transcriptional target c-Myc contributed to this metabolic switch. Based on these observations, CLL cells' acquired increased glucose dependency as well as Notch-c-Myc signaling could be therapeutically exploited in an effort to overcome stroma-mediated drug resistance.
EVALuna2:25708